From regular to irregular solid electrode surfaces : A systematic approach to their characterization - Arvia, Alejandro Jorge (1995)
A description of solid surfaces of interest for electrochemical reactions which is based on the analysis of scanning tunneling microscopy images is presented. Real single-crystal surfaces are better described as weakly disordered surfaces, in contrast to strongly disordered surfaces. Under certain conditions both anisotropic and isotropic strongly disordered surfaces exhibit fractal properties. The rationale of rough surfaces can be attempted by applying the dynamic scaling theory to analyze STM profiles. Examples from regular to irregular solid surfaces are given covering from real single-crystal and faceted metals to columnar structured and branched metal surfaces. Roughness caused by adsorbates and electropolymer coatings are also considered.